PERBANDINGAN SISTEM PENDIDIKAN DASAR DI INDONESIA DAN FINLANDIA - sumarni, sumarni (STAI YAPIS Takalar, 2024)
Indonesia seeks to improve the quality of education through the Merdeka Learning program, which gives teachers the freedom to innovate, be creative, and learn independently in carrying out the educational process. Education in Indonesia is still lagging behind when compared to other countries. Currently, education plays an important and main role for humans. The success of the Finnish education system, which has been recognized at the international level, demonstrates its superior quality. In contrast to Indonesia, there is a very striking difference in the education system. The research method used is a literature review, where data is collected from journals or books that are analyzed according to the problem discussed. Primary data was obtained through direct observation of children's activities in the early grade. In addition, secondary data were collected through literature review and analysis of documents related to the implementation of education systems in both countries. All data obtained were analyzed using the descriptive analysis method. The results of the study show that Finland receives extraordinary support from the government, which includes the provision of adequate school facilities, superior teacher qualifications, and guarantees of equality and equity in access to education. On the other hand, both Indonesia and Finland have uniqueness in their respective education systems that are adapted to the conditions, needs, and capabilities of their countries. Despite their differences, both have tried to implement the best education system to achieve optimal learning goals